Polemik Peraturan Pengeras Suara Masjid di Indonesia: Perspektif Agama sebagai Bagian Sistem Budaya - iqbal Ali Muzaky; Azis Muslim (Universitas Padjadjaran, 2023)
Islamic traditional activities will always intersect with interfaith communities. One of which is mosque loudspeakers that have been used for adhan at least five times a day. Mosque loudspeakers in some cultural setting, especially in rural communities, have been used to convey information rather than merely for adhan. However, in urban setting, the usage of mosque loudspeaker has been drawn pros and cons. Instead of providing peace, it creates noise in public spaces. Even in 2016, conflicts over mosque loudspeakers sparked and led to the burning of a worship center. The Minister of Religion issued a Circular Letter No. 05 of 2022 concerning the rules of mosque loudspeakers in order to prevent the re-emergence of inter-religious conflicts caused by mosque loudspeakers. This policy, however, has invited a polemic among public as it is considered lack of understanding of the cultural aspects behind the usage of mosque loudspeaker. This study aims to analyze the Circular Letter which is considered to have left cultural sociological consideration and seems to hegemonize the subcultures of urban communities over the traditional communities. The research applied to a literature study. This research found that the policy needs to be reviewed as it was considered not addressing the core of the problem.